2016
DOI: 10.1097/mpa.0000000000000490
|View full text |Cite
|
Sign up to set email alerts
|

Time Trend of Outcomes for Severe Acute Pancreatitis After Publication of Japanese Guidelines Based on a National Administrative Database

Abstract: This study shows that mortality of severe acute pancreatitis was reduced according to the time course, whereas LOS or medical costs were stable after publication of the Japanese guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…However, about 20% of cases are clinically severe [2]. Globally, in-hospital mortality rate of patients with severe acute pancreatitis (SAP) are estimated to be 5%-42% [3][4][5][6]. Patients with SAP usually present with fever, abdominal pain, subcutaneous bleeding, sepsis, and sometimes systematic inflammatory response syndrome and multiple organ dysfunction syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…However, about 20% of cases are clinically severe [2]. Globally, in-hospital mortality rate of patients with severe acute pancreatitis (SAP) are estimated to be 5%-42% [3][4][5][6]. Patients with SAP usually present with fever, abdominal pain, subcutaneous bleeding, sepsis, and sometimes systematic inflammatory response syndrome and multiple organ dysfunction syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Using the DPC database, previous studies have revealed the clinical practice of AP in Japan. [12][13][14] This study aimed to clarify the updated clinical practice of AP in Japan as well as its trend before and after the revision of the Japanese guidelines using the DPC database.…”
mentioning
confidence: 99%
“…The database includes basic hospitalization information such as age, sex, comorbidities at admission, dates of admission and discharge, history of admission to the intensive care unit (ICU), medications and interventional procedures, and outcomes at discharge. Using the DPC database, previous studies have revealed the clinical practice of AP in Japan 12–14 . This study aimed to clarify the updated clinical practice of AP in Japan as well as its trend before and after the revision of the Japanese guidelines using the DPC database.…”
mentioning
confidence: 99%